Exploring Risky Drinking and Knowledge of Safe Drinking Guidelines in Older Adults. (19th September 2014) - Gilson, Kim-Michelle; Bryant, Christina; Judd, Fiona
<x xml:space="preserve">Abstract</x> Background: Risky drinking criteria in older adults lack consistency across the literature. The variable definitions of risk have contributed in part, to widely differing prevalence estimates for risky drinking, ranging from 1% to 15%. Objectives: (1) To identify the prevalence of different types of risky drinking by applying several different criteria, (2) To investigate whether older adults have knowledge of the National Health and Medical Research Council recommended guidelines for safe drinking. Methods: The study population consisted of community dwelling past-year drinkers (n = 292) aged ≥60 years. Participants completed a postal survey on alcohol consumption using the AUDIT-C. Results: Applying multiple risky drinking criteria indicated that 6.6% to 31.7% of women and 21.6% to 44.8% of men were risky drinkers. Men were more likely than women to have inaccurate knowledge of the NHMRC guidelines, and nearly 59.2% of men who exceeded 14 drinks per week reported either not knowing the recommended limits or reported limits that exceeded the guidelines. Conclusions/Importance: A substantial number of older men drank at risky levels and overestimated safe drinking limits. Greater education on the vulnerability to alcohol-related harm together with greater screening practice by health professionals and service providers is recommended. Findings illustrate how different risky drinking criteria vary in their average AUDIT-C scores, with the NHMRC criteria showing greater average scores compared to other criteria. Results also imply that cutoff scores of ≥4 for women and ≥6 for men are consistent with a range of risky drinking criteria in older adults.